The Anthropological Story of Vučedol Culture(Early Bronze Age, Vučedol, East Croatia) - Hincak, Zdravka (Array, 2014)
Vučedol, the culture's eponymous settlement of the first half of the third millennium Before Christ (BC). The aim of this study was to complete the knowledge about life of Vučedol culture inhabitants with the help of biological anthropology, the wide unknown field which is still thereafter decades of archaeological excavation and research. Let's hold to evidences provided to us by well preserved skeleton remains of a few individuals, seven children and fourteen adult persons. From single to multiple grave funerary practices, through classic anthropological analysis of sex and age at death to usage of a different forensic methods, unique details were revealed. Special attention has been given to musculoskeletal stress markers, possible conditions and a manner of life, it's rhythm, and difficulties and pathological changes which all left their traces on the bone remains. We were following the asymptote of the Vučedol inhabitants life and death.